Active Contours Using Harmonic Global Division Function - Bhatti, M. T.; Soomro, S.; Bughio, A. M.; Soomro, T. A.; Anwar, A.; Soomro, M. A. (Engineering, Technology & Applied Science Research, 2019)
This paper presents the region-based active contours method based on the harmonic global signed pressure force (HGSPF) function. The proposed formulation improves the performance of the level set method by utilizing intensity information based on the global division function, which has the ability to segment out regions with higher intensity differences. The new energy utilizes harmonic intensity, which can better preserve the low contrast details and can segment complicated areas easily. A Gaussian kernel is adjusted to regularize level set and to escape an expensive reinitialization. Finally, a set of real and synthetic images are used for validation of the proposed method. Results demonstrate the performance of the proposed method, the accuracy values are compared to previous state-of-the-art methods.